ANALISIS TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MEMBACA DI PERPUSTAKAAN SEKOLAH PADA SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI PEKANBARU - Rawi Gunawan; Gimin Gimin; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by problems that arise from observationsmade by researchers according to the reality that occurs in the field, indicating that thelack of attention to the condition of the library is often the cause of obstacles forstudents in enriching their knowledge through existing library materials as a means ofincreasing knowledge . The formulation of the problem in this study is "How is theinterest in reading in the school library for students in Pekanbaru State Junior HighSchool?". This study aims to determine what factors influence reading interest in theschool library for students at Pekanbaru State Junior High School. This research wasconducted at Pekanbaru State Junior High School in February-March 2020. Thepopulation in this study were 44 schools totaling 29025. The sample in this study was268 students. In this study, researchers used stratified random sampling. Readinginterest in the library of students at SMP Negeri Pekanbaru is influenced by severalfactors, namely respondents to the physiological factor variable which are in the highcategory, namely 119 respondents or (44.4%), the intellectual factor variable is in themoderate category, namely as many as 112 respondents or (41.8%), the environmentalfactor variable is in the medium category, namely 148 respondents or (55.2%) while thepsychological factor variable is in the High category, namely as many as 142respondents or (53%). The test results of multiple linear regression analysis show thatthere is a significance value of 0.004 <0.05, which means that there is an influence ofphysiological factors on students' reading interest in the school library. The test resultsof multiple linear regression analysis show that the intelligence factor variable has asignificance value of 0.000 <0.05, which means that there is an influence ofenvironmental factors on students' reading interest in the school library. The test resultsof multiple linear regression analysis show that the environmental factor variable has asignificance value of 0.000 <0.05, meaning that there is an influence of environmentalfactors on students' reading interest in the school library. The test results of multiplelinear regression analysis show that the psychological factor variable has asignificance value of 0.001 <0.05, meaning that there is an influence of psychologicalfactors on students' reading interest in the school library.Key Words: Library Function Implementation, Reading Interest